THE STRUGGLE OF IDEAS AND «THE NEW TURKEY» - V. A. Nadein-Raevskiy (Vestnik MGIMO-Universiteta)
A famous Islamic philosopher Fethullah Gulen backed up the nowadays president Erdogan in the beginning of creation of his Justice & Development Party (AKP). Gulen though backed up Erdogan criticized some of his actions. He was against the "Freedom Flotilla" that was sent be Erdogan to raise the blockade of Gaza sector. He visited the Roma Pope while defending the idea of the "Dialog of civilizations" and was sharply criticized for this visit by the Islamists. In 2013 he criticized Erdogan for the police attacks against mass demonstrations of protest in Istanbul. Besides he sharply criticized corruption of the AKP officials. Erdogan was irritated by this criticism. In spite of many common ideas of contemporary «moderated Moslems» - the supporters of Erdogan and followers of Gulen severe inter-political struggle among them lead to massive attacks against gulenist's "Hizmet" Movement and Nurcilar (Nur movement - the followers of anti-secular cleric Said Nursi). In respond "Hizmet" started a broad campaign against corruption and nepotism among the Erdogan's supporters. The latter charged gulenists in conspiracy activities against the ruling party and "betrayal of Turkey". They closed gulenist's educational schools and started the cleansing campaign against "Hizmet" in the state structures. This struggle may influence on the ideologic basement and the future of Turkey.